The relationship between job stress and job performance among the employees in school of medical science at USM Kubang Kerian, Kelantan / Razehah Md Rashid - Md. Rashid, Razehah (2015)
Stress is an integral part of human life where people live with it, deal with itand above all worry about it. Each person faces stressful situations from time to time and it is important to accept the fact that stress can never be completely eliminated. In fact, stress can be a silent killer to a person who is unable to handle the stress that can lead to many negative impacts in people's life. The word stress is often used to describe almost everything that seems to become too much and overload and wonder whether the person really can cope with the pressures placed upon them. According to McShane, Olekalns and Travaglone (2013), "stress is a physiological and psychological condition that prepares us to adapt to hostile or noxious environmental conditions". Besides that, McShane et al., (2013) also stated that "stress is an adaptive response to a situation that is perceived as challenging to a person's wellbeing". Meanwhile, from the view of Carr, Kelley, Keaton and Albrecht (2011), *"stress is what sharpens your concentration while play1ng a game or keeps you on your toes during a work presentation". In general, something that evokes a challenge or a threat to the person wellbeing is a stress, but in a certain situation, stress can get the people going and this is good for them. This is because without any stress, people's life would be boring and they would probably feel pointless.